2021
DOI: 10.1017/s2040174421000611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal exposure to acute stress on birth outcomes: a quasi-experiment study

Abstract: Numerous studies have shown associations between maternal stress and poor birth outcomes, but evidence is unclear for causal inference. Natural disasters provide an opportunity to study effects of quasi-randomized hardship with an accurate measure of onset and duration. In a population-based quasi-experimental study, we examined the effect of maternal exposure to the January 1998 Québec ice storm on birth outcomes by comparing pregnant mothers who lived in an area hard hit by the ice storm with those in two un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…22 However, a study using administrative data in Quebec, Canada, failed to find any association between birth outcomes and prenatal exposure to a major ice storm that deprived 3 million people of electricity for as long as 45 days in the middle of winter. 23 Importantly, studies using administrative data cannot determine which aspects of the maternal experience account for any effects of prenatal maternal exposure to a disaster on birth outcomes. In a smaller study of the Quebec disaster, Project Ice Storm, researchers assessed the magnitude of pregnant women's experiences of disaster-related objective hardship and subjective distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 However, a study using administrative data in Quebec, Canada, failed to find any association between birth outcomes and prenatal exposure to a major ice storm that deprived 3 million people of electricity for as long as 45 days in the middle of winter. 23 Importantly, studies using administrative data cannot determine which aspects of the maternal experience account for any effects of prenatal maternal exposure to a disaster on birth outcomes. In a smaller study of the Quebec disaster, Project Ice Storm, researchers assessed the magnitude of pregnant women's experiences of disaster-related objective hardship and subjective distress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a population register study of births in Chile before and after a major earthquake suggests that significant effects of earthquake exposure on low birth weight are mediated by effects on shorter gestational age 22 . However, a study using administrative data in Quebec, Canada, failed to find any association between birth outcomes and prenatal exposure to a major ice storm that deprived 3 million people of electricity for as long as 45 days in the middle of winter 23 …”
Section: Discussionmentioning
confidence: 99%
“…Both the level and unpredictability of material hardship were significantly associated with worsened emotional well-being in families with young children during the COVID-19 pandemic, and these associations were partly mediated through disrupted family routines. The global pandemic and other large-scale socio-historical events are frequently approached as natural experiments because they are imposed on a broad swath of the population independent of the actions of the individual (e.g., Ahmed et al, 2021 ; Zahran et al, 2014 ). Consistent with the “natural experiment” framework of the pandemic, these findings can be leveraged to advance the scientific understanding of early adversity ( Roubinov et al, 2020 ; Thomson, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study in New York City demonstrated that among patients who were in their first trimesters during the World Trade Center attack on September 11, 2001, gestations were slightly shorter (−3.6 days), but the study did not report PTB rates [ 29 ]. Ahmed et al assessed if exposure to an ice storm in Quebec increased the risk of PTB and if trimester at exposure modified this association [ 30 ]. No differences in the rate of PTB was observed between exposed and non-exposed individuals and no trimester-specific effect was observed.…”
Section: Discussionmentioning
confidence: 99%